AN ANALYSIS OF TEXTUAL MEANING REALIZATION IN THEME SYSTEM AND STRUCTURE OF SPOKEN TEXT DELIVERED BY NADIM MAKARIM DURING COVID-19 - Ngongo, Magdalena; Ndandara, Alfriani (English Education Study Program - Artha Wacana Christian University, 2023)
This article is aimed to describe textual meaning realization in system and structure of spoken texts delivered by Nadim Makarim during covid-2019. Oral data were obtained through observation taken from you tube. There were five texts to be observed and analysed. All data were analysed using descriptive qualitative method and results were presented using formal and informal method. The results showed that text theme realizing textual theme, system and structure. The total number of theme was 382 consisting of 127 topical theme, 217 textual, and 38 interpersonal theme. The more use of textual theme was caused by tenor’s aim to give deeply explanation of the message stated in order to be paid attention and considered by listeners.. The less use of interpersonal theme was caused by tenors’ position as if speaker and listeners are closed even though via online. This text also used marked and unmarked themes. Marked theme that were used in texts were complement and adverbial. The use of marked theme was aimed to specify an object or adverbial as important thing. Text thematic structure of text consists of four variations